PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE EVERYONE IS A TEACHER HERE TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK SISTEM REPRODUKSI (Penelitian Quasi-experiment design di Kelas XI SMA Negeri Jatinangor) - Iis Yuniarti; Ara Hidaya; Meti Maspupah (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2015)
Student learning outcomes in schools is often indicated with learning problems of these students in understanding the material. Indication is made possible because of the lack of effective student learning, even the students themselves do not feel motivated to follow inthe classroom. In this research can help to overcome the existing problems, the implementation of cooperative learning model Everyone is a teacher here. The method used in this study is the method of Quasi-experimental design. The study design used was a nonequivalent control group pretest-posttest means researchers treated and make observations. Population taken is class XI Science. Data collection technique is done with thetest. The research proves that learning model everyone is a teacher here can be a positive influence on learning outcomes of students in the subject matter of the reproductive system, with the average value of the posttest in the class that uses the model everyone is a teacher here 76.29 with both category and value gain 33 , 43. In classes without a model the averageposttest score 69.43 with enough categories and gain value 26.86. To test the hypothesis shows that T_hitung amounted to 2.38> T_tabel of 1.67, so it can be concluded that the cooperative learning model everyone is a teacher here a positive effect on learning outcomes of students in the subject matter of the reproductive system.